The Feasibility of Staple Food Business and Its Implication on Regional Food Supply Chain Development - Sutrisno Sutrisno (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
The purpose of this research is to find out the investment feasibility of developing staple food businesses in the rural area of Bojonegoro regency, to review the financial aspects and to calculate the investment feasibility.  This research used four types of analysis namely trend analysis, aspects of the investment, the investment feasibility and sensitivity. The results of the research show that there was an increase in the economic growth of 26.50 percent per year during 2016-2019, IRR  37.2 percent, positive NPV, the payback period was fewer than 5 years. The sensitivity analysis shows that the possibilities of an increase in operational costs of 2 percent produced NPV 34.7 million rupiahs and the IRR  36.97 percent, an increase such costs of 4 percent produced NPV 33.9 million rupiahs and the IRR 36.62 percent.  Meanwhile, the possibilities of a decrease in income of 2 and 4 percent find NPV 32.4 million rupiahs and the IRR 35.99 percent; and NPV value was 29,3 million rupiahs and the IRR 34.59 percent respectively.  The results indicate that the staple food business in Bojonegoro regency was considered feasible.  Furthermore, this research has implications for regional food chain development in terms of the stability of domestic food production, stabilization of food prices, regulation of space infrastructure improvements and business climate of investment. JEL Classification: D19, J54, Q12